Correlating damage progression to fragmentation at high strain rates using molecular dynamics. (23rd January 2020) - Huddleston, B D; Dickel, D E; Williams, Neil; Danielson, Kent; Hammi, Y; Bowman, A L; Baskes, M I; Horstemeyer, M F
Abstract: We show a correlation between nanoscale void nucleation and the fragment size by employing atomistic simulations that isotropically expand copper with a varying number of uniform grains at various strain rates and temperatures. Damage within the simulation was quantified in terms of the void number density (void nucleation) and void volume. We quantified the fragment size in terms of a length scale parameter defined as the solid volume-per-surface-area. The relationship of the fragment size to the strain rate was compared to existing models and was found to follow a −1/2 power law. At the atomic scale, the void number density is shown to increase with increasing strain rate, increasing temperature, and decreasing grain size. A fundamental relationship between fragmentation and the internal damage structure is suggested by the correlation between the fragment size and the maximum void number density of a −1/3 power law. We can upscale the relationship between void nucleation and fragmentation observed in molecular dynamics to higher length scales by using the length scale-appropriate models for damage evolution.